Development of Digital Competences in Teachers of Basic and Secondary Education (Docentes 2.0 Journal, 2022)
The current knowledge society demands new abilities in human beings that guarantee their survival. The popularization of digital tools and the Internet has changed the distribution of knowledge; a change in the leading role of teachers is required. The general objective was to design the proposal based on identifying training needs, from the pedagogical, technological components, and of course, the elements that structure the reality of the population. The population is the community of the Pablo VI Rural Educational Institution of the Santa Isabel de Hungary district of the municipality of Remedios - Antioquia; specifically, teachers and directors of primary education in the official sector. The research was developed under the Humanist paradigm, inductive method, qualitative approach, biographical design, informative documentary type, and cross-section. A documentary review was carried out; so that antecedents, variables, areas, and functions linked to digital teaching skills were identified. The techniques used to collect information were proposed through two unique surveys, designed based on global order requirements; second, semi-structured interviews. The established categories of analysis are linked to the four essential functions of digital teaching skills and contributions from various references. The findings, which showed a medium-low level of the skills in question, became a core input in the foundations of the proposal's design.
Keywords: Digital skills; teaching skills; educational innovation; pedagogical practice